Reinforcing ion diffusion and controlling microcrack of nickel-rich cobalt-free single-crystalline cathodes via interfacial protection and bulk optimization - Zheng, Chao; Xiao, Zhiming; Xian, Keyi; Wen, Heng; Lu, Na; He, Xinyou; Ye, Long; Du, Kejie; Zhang, Bao; Ou, Xing; Wang, Chunhui (Journal of colloid and interface science, 2025)
[Display omitted] •The synchronous modification strategy from interface to interior for ultrahigh-Ni Co-free cathode.•The Sb-based modification can enhance structure stability both interface and bulk of materials.•Unbroken layer structure and enlarged ion channel improve the reaction kinetics of designed materials. Nickel-rich cobalt-free layered oxide cathode with Ni contents no fewer than 90 % has received extensive attention in the field of lithium-ion batteries due to its excellent specific capacity and low cost, but serious capacity degeneration induced by structural deterioration and interfacial instability greatly hamper their further development. Herein, the Sb-modified LiNi0.9Mn0.1O2 materials from the interface to interior have been designed and fabricated to overcome the above issues. On the one hand, the introduction of Sb-ion in interior of grains can generate Sb-O chemical bond with high dissociation energy, which contributes to reinforce the chemical and structural stability. Meanwhile, the existence of Sb-ions can restrain the harmful H2-H3 phase transformation and expand interlayer spacing, thereof enabling to weaken the mechanical stress and enhance ion diffusion rate. On the other hand, the surficial modification resulted by the Sb-based materials can effectively suppress the noxious interfacial reaction, which is conducive to improving the cycling stability. As expected, the capacity retention rate of NM-Sb materials prepared by this optimized design in this work reached 89.5 % after 200 cycles at 1 C. Thus, the constructed double-modification is essential for obtaining robust framework and enhancing interfacial stability for high-performance nickel-rich cobalt-free lithium-ion battery cathode materials.